The phantom of the cinema : character in modern film - Michaels, Lloyd (Albany : State University of New York Press, 1998)
Films discussed include Jules and Jim, Escape from Alcatraz, The day of the jackal, Reservoir dogs, Persona, The magician, House of games, Nosferatu: a symphony of horror, Nosferatu: the vampyre, Reilly: ace of spies, The mystery of Kaspar Hauser, The thin blue line, Lacombe, Lucien, Daddy Nostalgia, Mephisto, Badlands, Days of Heaven, Five Easy Pieces, and The lacemaker.
The phantom of cinema: representation of character in the modern film -- Reflexivity and character in Persona -- Incarnations of the confidence man -- Reviving the undead: Herzog's remake of Nosferatu -- The spy and the cipher -- Documenting character in The thin blue line -- Avatars of memory: entropy and nostalgia in the representation of character -- Conclusion: the mystery and melancholy of a self.
Includes bibliographical references (pages 173-180) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Characters and characteristics in motion pictures; Personnages au cinéma.; PERFORMING ARTS -- Film & Video -- Reference; Characters and characteristics in motion pictures